House price estimation using hedonic approach for mass appraisal model in Minna, Nigeria - Liman, Hassan Shuaibu (2014)
The purpose of this research is to develop a mass appraisal model for house price estimation using hedonic price modelling approach for Minna, Nigeria. Three basic micro determinants of house price were considered namely structural, locational and neighborhood attributes. Using a sample of 91 transaction data recorded between 2009 to 2013, the hedonic based multiple regression analysis (MRA) was used to determine the variables that have statistically significant influence on price of a house. It was established that all the variables included in the MRA were significant except the number of rooms. The significant variables were the type of house, the size, number of bathrooms, location, age, year of transaction, condition of the house, its distance to the central business district (CBD) and the neighborhood facilities available. Using these significant attributes, a mass appraisal model for residential property taxation was developed for the study area. The performance of the model was evaluated using the ratio study technique and the model was found to be adequate. It was recommended that this model be used in mass appraisal of residential properties in Minna in the future, with a view to improve accuracy, efficiency and fairness of the real property tax system, which will lead to generating more revenue for the government which will foster physical infrastructural development in Minna.